ANALISIS KETERAMPILAN LITERASI MEMBACA DIGITAL GENERASI Z DALAM MENGIDENTIFIKASI BERITA HOAKS DI ERA DIGITAL - Maryani, Sri; Wulandari, Ratna Rizky (Jurnal TEDC, 2025)
This study aims to analyze Generation Z's digital reading literacy skills in identifying hoaxes in the digital era, where information spreads rapidly across various platforms. Employing a qualitative approach with descriptive analysis methods, this research involved 74 respondents from Generation Z, born between 1997 and 2012. Data were collected via a questionnaire to evaluate their understanding and practices regarding hoax news. The research findings indicate that 98.6% of respondents are aware of hoaxes, and 89.2% verify information before accepting it. However, only 64% feel confident in their ability to assess the credibility of information sources. Social media, particularly WhatsApp and TikTok, were identified as the main news sources, which potentially increases the risk of exposure to inaccurate information. These findings indicate a gap between awareness and evaluative skills possessed by Generation Z. Therefore, developing more comprehensive digital literacy programs in schools and communities is deemed necessary to enhance their critical abilities in confronting potentially misleading information. This study proves that without adequate digital reading literacy skills, Generation Z is at risk of being caught in the tide of misinformation that could influence political views, health perspectives, and other social issues.